Championing Equity, Empowerment, and Transformational Leadership in (Mental Health) Research Partnerships: Aligning Collaborative Work With the Global Development Agenda - Kumar, Manasi (Frontiers in Psychiatry, 2019)
Through a narrative synthesis of existing literature on research partnerships, the paper underscores four core values championed in public policy and practice: equity, empowerment, transformational leadership, and treating mental health research as a cooperative inquiry. Building on these values, the author maps the challenges before mental health researchers in forging resilient, egalitarian, and committed Global North-South partnerships within the context of current global development agenda. Reports appraising the UN Millennium Development Goals lament how the goal of developing global partnerships to combat health, gender, and economic inequities has remained under-realized. Emphasis has been placed on the great need to augment Sustainable Development Goals (SDG) in ways where partnership processes would drive development and human rights agenda for the most afflicted, under-resourced, and marginalized in the world. Global North-South partnerships result in fewer lasting benefits to Global South – a regressive trend that is critically analyzed. The need for Global North to adopt ethical and responsible stances while creating/curating new knowledge is discussed. being responsible is not only imperative for Global North researchers; it is imperative for both North and South researchers to adopt a dialogical approach in clarifying and sharing roles, responsibilities, access, and leadership in developing scholarship and praxis in mental health. The importance of de-centering hierarchies, valuing reciprocity in one another, improving communication, demonstrating empathy, and sharing resources and benefits are found to be key components in the narrative synthesis towards achieving greater empowerment and equity. The paper reflects on the potential problems in engagement and development of de-centered and transformational leadership in partnerships and implications for research ethics in the context of lower-and-middle-income countries. Lastly, the author in a bid to encourage global partnerships suggests that engaging in transparent and bi-directional conversations regarding these issues and realigning research priorities along the four core values will contribute to greater success in research collaborations (across cultural contexts) and more so in the global mental health field.